Targeting survivin sensitizes cervical cancer cells to radiation treatment. Issue 1 (1st January 2020) - Zhou, Jing; Guo, Xiaojing; Chen, Weifen; Wang, Liming; Jin, Yonglong
ABSTRACT: Survivin is an inhibitor of apoptosis protein that functions to inhibit apoptosis, promote proliferation, and enhance invasion. It is selectively up-regulated in many human tumors and implicated in cellular radiation response through its role in apoptosis, cell division, and DNA damage response. This study aimed to investigate the effect and mechanisms of targeting survivin radiosensitivity in cervical cancer C33A cells. Here, the authors designed a small interfering RNA (siRNA) or plasmid-based small hairpin RNA (shRNA) targeting survivin and tested its effects on radiosensitivity to ionizing radiation (IR) treatment of C33A cells in vitro, as well as on the tumorigenicity of C33A cells in nude mice in vivo . Transient transfection of survivin siRNA into C33A cells suppressed survivin expression, induced cell apoptosis and G2/M arrest and reduced cell proliferation, clone formation ability after IR, followed by p53 upregulated modulator of apoptosis (PUMA) upregulation. But, transient transfection of survivin siRNA alone has no significant effect on cell growth and apoptosis. To confirm that PUMA upregulation is necessary for survivin silencing -induced radiosensitivity to IR treatment, the effect of targeting PUMA in survivin sliencing cells was observed. The results showed that targeting PUMA in survivin sliencing cells rescued C33A cells' radioresistance. Furthermore, knocking down survivin expression combined with IR treatment significantly slowed tumor growth and promoted tumor cell apoptosis in C33A xenografted tumors. It was concluded that survivin played a role in radiotherapy resistance. Targeting survivin increased the radiosensitivity of C33A cells through induction of PUMA expression. Graphical Abstract: